Experimental research on mechanical properties of desert sand steel-PVA fiber engineered cementitious composites - Che Jialing; Li Quanwei; Lee Minggin; Wang Dan (Functional Materials, 2017)
An orthogonal experimental design method involving five-factor and four-level is adopted for the mix design of Desert Sand Steel-PVA fiber ECC. The effect of each level on Mechanical properties of ECC and the difference of Mechanical properties between each level is analyzed. The influence of different experimental factors is discussed, which includes water-binder ratio, fly ash substitution rate, desert sand substitution rate, proportion of PVA fiber and proportion of steel fiber. The experimental results indicate that water-binder ratio and fly ash substitution rate are the most principal and significant influencing factors on the compressive strength of ECC, regardless of age. Steel fiber is conducive to development of splitting tensile strength; PVA fiber is conducive to the development of flexural strength. High strength ECC can be prepared when the desert sand substitution rate is high. As the raw material of ECC, river sand can be 90% replaced by desert sand.